Dictionary of archaeological terms : English-French/French-English = Dictionnaire des termes archéologiques : anglais-français/français-anglais - Clodoré-Tissot, Tinaig, (Archaeopress, 2012)
This dictionary - an assemblage of more than 10,000 archaeological words and terms - is intended to assist in the reading of archaeological books and publications (from the Paleolithic to the Middle Ages), and in the writing of papers and articles in both English and French. The aim is to help, in particular, students and archaeologists in the field to find quickly words relating to a specific period, a specific area, or a research field. Of course, the dictionary is also for everyone fond of archaeology, from Prehistory to the Middle Ages.